Enhancement of mass transfer in a proton exchange membrane fuel cell with blockage in the flow channel - Shen, Jun (2021)
Flow field design is very important for performance enhancement of a proton exchange membrane fuel cell (PEMFC). The most common method for the evaluation of the improved performance of a particular PEMFC design is the polarization curve. The principle of field synergy based on enhanced mass transfer theory is introduced and applied to flow channel design in this study. A single PEMFC with different flow patterns was used to validate the theory both numerically and experimentally. Compared with a PEMFC having a conventional single serpentine flow field, the performance of a PEMFC with four different blockages in the flow channel was investigated in detail. Based on the field synergy principle, the synergy angle and effective mass transfer coefficient were defined to verify the results. With the addition of blockages, the average synergy angle between the gas velocity and the concentration gradient at the cathode decreased, while the effective mass transfer coefficient improved, thus enhancing the performance of the PEMFC. This novel use of the principle of field synergy offers a new dimension for optimizing the flow field design for PEMFCs.